Estratégias para implementação de governança ambiental no Refúgio de Vida Silvestre Mata do Junco, uma Unidade de Conservação Estadual de Sergipe - Silva, Carlos Miranda da (2016)
The conservation of biodiversity is closely linked to the maintenance of the natural resources and the strategies for protection of these natural assets. Among the Brazilian biodiversity protection mechanisms there are the Conservation Units (UCs), established by Law 9.985/ 2000, which regulates the National System of Protected Areas of Nature (SNUC). However, only the implementation of these are as does not guarantee its maintenance, it is necessary the effective and representative participation of the social actors that are embedded within its management, i.e. the managing council, given the purposes that subsidized the creation of such protected areas. The Wildlife Refuge Mata do Junco (RVSMJ) is a Conservation Unit administered by the Ministry of Environment and Water Resources of Sergipe (SEMARH / SE), in the municipality of Capela, state of Sergipe, with the objective of protect the headwaters, vegetation, and shelter animal species, including the Callicebus coimbrai (titi monkey) an endangered species. In addition to this UC has as its major management tools the management plan and the consultative council. In this context, this study aimed to evaluate the monitoring of the strategic actions identified by the Socio-Environmental Indicator System for Conservation Units (SISUC), through its consultative council, to contribute for the adaptive management of the RVSMJ. And also understand the level of social representation that the council has on the UC and on their management by verifying what are the consensus and conflict components, aided by the Social Representation Theory. The use of this tool SISUC UC pointed out two indicators that are in alarming situation and two underun satisfactory situation, which unfolded in six actions proposed by the Council members so that these indicators could be monitored and improved. Of the six proposed actions, four have being carried out and two did not succeed. However, the implementation of this tool can be considered valid since it was successful in the majority of actions as well as the use of this tool provided the empowerment and autonomy of the social actors. Thus, it can be considered that the evidence presented by the directors in relation to their social representations about the RVSMJ, the advisory board and the management of this Conservation Unit encourage their participation and thus contributes to the improvement in the process of management and consequently foster governance processes that permeate this course, and in turn contributes to the maintenance and conservation of biodiversity.